Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto. Issue 7 (3rd April 2022) - Xie, Yang; Yao, Xiao-Chang; Tan, Lei-Hong; Long, Hong-Ping; Xu, Ping-Sheng; Li, Jing; Tan, Gui-Shan
Abstract: A chalcone-flavonone type biflavonoid, trichocladabiflavone A (1 ), along with eight known biflavonoids (2–9 ) were isolated from the 70% EtOH extract of Selaginella trichoclada . Their structures were elucidated by extensive spectroscopic analyses. Compound 1 was the first chalcone-flavonone type biflavonoid reported in the genus Selaginella . Moreover, compound 1 exhibited moderate cytotoxicity against DU145, MCF-7 and PC3 human cancer cell lines. Graphical Abstract: